1999
DOI: 10.1074/jbc.274.48.34337
|View full text |Cite
|
Sign up to set email alerts
|

Human 75-kDa DNA-pairing Protein Is Identical to the Pro-oncoprotein TLS/FUS and Is Able to Promote D-loop Formation

Abstract: Homologous recombination plays a fundamental role in DNA double-strand break repair. Previously, we detected two mammalian nuclear proteins of 100 and 75 kDa (POMp100 and POMp75, respectively) that are able to promote homologous DNA pairing, a key step in homologous recombination. Here we describe the identification of human (h) POMp75 as the pro-oncoprotein TLS/FUS. hPOMp75/TLS binds both single-and doublestranded DNAs and mediates annealing of complementary DNA strands. More important, it promotes the uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
128
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(130 citation statements)
references
References 47 publications
2
128
0
Order By: Relevance
“…Although other studies have implicated a role for FUS in maintaining resistance to genotoxic stress, possibly via participation in HR repair (34,40,41), the present results indicate that FUS functions are required for optimal DSB repair through both NHEJ and HR. FUS joins a growing list of RNA-processing factors including RBMX, PPM1G, THRAP3, hnRNPUL1 and -2, and NONO, that are recruited to the proximity of DSBs and whose activities are required for genotoxin resistance and DNA repair (51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Although other studies have implicated a role for FUS in maintaining resistance to genotoxic stress, possibly via participation in HR repair (34,40,41), the present results indicate that FUS functions are required for optimal DSB repair through both NHEJ and HR. FUS joins a growing list of RNA-processing factors including RBMX, PPM1G, THRAP3, hnRNPUL1 and -2, and NONO, that are recruited to the proximity of DSBs and whose activities are required for genotoxin resistance and DNA repair (51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 54%
“…Previous work has shown that FUS is capable of supporting D-loop formation, which suggests a potential role in HR (34). To test this we used the HEK-293 DR-GFP reporter cell line, which specifically measures repair through HR (46).…”
Section: Fus Promotes Efficient Dsb Repair-fusmentioning
confidence: 99%
See 2 more Smart Citations
“…These data agree with a role of TLS in transcriptional regulation. TLS has been biochemically characterized as hPOMp75, a protein involved in homologous DNA pairing and recombination (Baechtold et al, 1999;Bertrand et al, 1999). This activity fits with the increased sensitivity to ionizing radiation due to chromosome pairing defects during meiosis in the TLS-deficient mice suggesting that TLS could participate to the maintenance of genomic integrity (Kuroda et al, 2000).…”
Section: Introductionmentioning
confidence: 86%